Apnoeic oxygenation with high flow nasal oxygen for interventional surgery of the larynx and pharynx - Langer, Christine; Wittekindt, Claus; Arens, Christoph; Käbisch, Sonja; Justus Liebig University Giessen (My University, 2024)
Background: Highflow nasal cannula oxygen (HFNO) is known to be used for noninvasive oxygenation in intensive care patients but it has rarely been used in airway management for elective surgery of the upper aerodigestive tract. Objectives: HFNO offers opportunities of a tubeless oxygenation system which is easy to handle and not limited only on surgery of the endolarynx. Methods: We evaluated this method for oxygenation during brief interventional procedures of the larynx and pharynx in 92 adult patients for safety and intraoperative complications. The need of secondary endotracheal intubation and limiting comorbidities as pulmonal and cardiac diseases were documented. Results: HFNO showed a good safety profile concerning saturation and hypercapnia. Oxygen desaturation below 90% occurred only in 5 patients, mask ventilation led to quick recovery except in one patient who was secondary intubated. A significant influence of the body mass index on the minimal O2 saturation was shown (p < 0,001) so that a possible limitation of the method exists here. Comorbidities were grouped into the ASA classification. There was a significant difference between ASA I/II and ASA III patients in terms of minimum O2saturation. Conclusion: We conclude that HFNO may hold great promise for changing ventilator technique in general anesthesia, particularly in short elective laryngeal and pharyngeal surgery. Safety and feasibility were proven in this study.
Keywords: ddc:610